Analisis Peluang Dan Tantangan Indonesia Dalam Pasar Kreatif Global Di Era Digital - David Dermawan Zebua (Jurnal Ilmu Manajemen dan Akuntansi Nusantara, 2026)
The creative economy has become one of the new pillars of Indonesia's national economic growth. With its abundant cultural wealth and increasing internet penetration, Indonesia has great potential to become a key player in the global creative market. This study aims to analyze the opportunities that can be exploited and the significant challenges facing Indonesia. Using qualitative descriptive methods, the analysis shows that despite Indonesia's superior cultural diversity and productive population, barriers such as digital infrastructure, intellectual property rights regulations, and international quality standards remain major obstacles.